2023
DOI: 10.1039/d2cy01667b
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid-mediated hexagonally porous ZnO nanocrystal-supported Au catalysts: highly stable materials for aldehyde oxidative esterification

Abstract: Ionic liquid-mediated hexagonally porous ZnO nanocrystal-supported Au catalysts: highly efficient and stable materials for oxidative esterification of methylacrolein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Procedure for the preparation of porous cerium oxide solid solution catalysts by ionic liquids(a); TEM image of porous cerium oxide loaded with gold(b)Ce; [19] SEM(c) and TEM (d) images of hexagonal porous zinc oxide loaded with gold catalysts prepared by ionic liquids. [19,38] (The catalyst carrier in a,b is CeO; The catalyst carrier in C,D is ZnO) making them suitable as solvents and catalysts for homogeneous reaction systems with high reactivity. Han's group [92] utilized the ionic liquid 1-ethyl-3-methylimidazole acetate ([EMIM]OAc) as a catalyst for alcohol self-esterification or crossoxidative esterification with high reactivity, they found that the anion and cation of alkaline ionic liquid ([EMIM]OAc) can significantly activate the hydroxyl group of alcohols in the substrate through the interaction of intermolecular hydrogen bonding, and the synergistic effect makes activated hydroxyl groups oxidize under mild conditions, and the [EMIM]OAc can be oxidized under mild conditions.…”
Section: Ionic Liquid Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…Procedure for the preparation of porous cerium oxide solid solution catalysts by ionic liquids(a); TEM image of porous cerium oxide loaded with gold(b)Ce; [19] SEM(c) and TEM (d) images of hexagonal porous zinc oxide loaded with gold catalysts prepared by ionic liquids. [19,38] (The catalyst carrier in a,b is CeO; The catalyst carrier in C,D is ZnO) making them suitable as solvents and catalysts for homogeneous reaction systems with high reactivity. Han's group [92] utilized the ionic liquid 1-ethyl-3-methylimidazole acetate ([EMIM]OAc) as a catalyst for alcohol self-esterification or crossoxidative esterification with high reactivity, they found that the anion and cation of alkaline ionic liquid ([EMIM]OAc) can significantly activate the hydroxyl group of alcohols in the substrate through the interaction of intermolecular hydrogen bonding, and the synergistic effect makes activated hydroxyl groups oxidize under mild conditions, and the [EMIM]OAc can be oxidized under mild conditions.…”
Section: Ionic Liquid Catalystmentioning
confidence: 99%
“…Ionic liquids were used as templating agents to prepare cerium oxide solid solutions with porous rod‐like Mn doping and apply them to the oxidative esterification reaction of aldehydes to esters in Figure 11 [19] . Hexagonal zinc oxide with porous structure was prepared by CTAB (Hexadecyl trimethyl ammonium Bromide) and ionic liquid as template agent, and C 10 mimCl (ZnO nanorods with hexagonal pores have been synthesized by the hydrothermal method assisted by ionic liquids (ILs) with different alkyl chain lengths) as template agent can prepare unique hexagonal pore structure, which improves the dispersion and stability of nanogold in Figure 11 [38] . It indicates that ionic liquid as template agent has a unique role.…”
Section: New Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of MMA via one-step oxidation and esterification of methacrolein with methanol is a green and sustainable way, which has a high atom utilization rate, no pollution, and environmental friendliness, and has attracted wide attention in recent years [6][7][8][9][10][11][12]. The construction and modification of gold catalysts have shown excellent performance in CO oxidation reactions [13,14], oxidative esterification reactions [15][16][17][18][19][20][21], and other fields. However, the alkaline sites of the support in gold-based catalysts, the particle size of gold nanoparticles, and the interaction between the support and gold nanoparticles all have a certain impact on the reaction performance.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction was carried out under neutral conditions with a MAL conversion of 58% and MMA selectivity of 98% . After this, a variety of materials were adopted to support Au nanoparticles, such as La 2 O 3 , ZnO, , MgO, CeO 2 , Ce 0.6 Zr 0.4 O 2 , , and HVP . However, most of the catalysts could not achieve both high reactivity and selectivity, and most reactions also required a large amount of catalyst.…”
Section: Introductionmentioning
confidence: 99%